2009
DOI: 10.1007/s00299-009-0810-3
|View full text |Cite
|
Sign up to set email alerts
|

Selection system and co-cultivation medium are important determinants of Agrobacterium-mediated transformation of sugarcane

Abstract: A reproducible method for transformation of sugarcane using various strains of Agrobacterium tumefaciens (A. tumefaciens) (AGL0, AGL1, EHA105 and LBA4404) has been developed. The selection system and co-cultivation medium were the most important factors determining the success of transformation and transgenic plant regeneration. Plant regeneration at a frequency of 0.8-4.8% occurred only when callus was transformed with A. tumefaciens carrying a newly constructed superbinary plasmid containing neomycin phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 21 publications
1
36
0
5
Order By: Relevance
“…The Basta gene-based selection system brought about an easy and reproducible selection method and it has successfully produced numerous herbicide-resistant transformed crops e.g. oilseed rape (De Block et al 1989;Kopertekh et al 2009), sugarcane (Joyce et al 2010), cassava (Koehorst-van Putten et al 2012) and tomato (Khuong et al 2013). Unfortunately, most of the vectors that contain Basta as a plant selectable marker are gateway based vectors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Basta gene-based selection system brought about an easy and reproducible selection method and it has successfully produced numerous herbicide-resistant transformed crops e.g. oilseed rape (De Block et al 1989;Kopertekh et al 2009), sugarcane (Joyce et al 2010), cassava (Koehorst-van Putten et al 2012) and tomato (Khuong et al 2013). Unfortunately, most of the vectors that contain Basta as a plant selectable marker are gateway based vectors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that the effectiveness of transformation via different strains of Agrobacterium can be significantly different (e.g., De Bondt et al 1994;Le Gall et al 1994;Bond and Rose 1998;Cervera et al 1998;Gill et al 2004;Petri et al 2004;Joyce et al 2010). Several Agrobacterium strains, including LBA4404, EHA101, EHA105, GV3101, have been used in plum transformation previously (Mante et al 1991;Padilla et al 2003;Petri et al 2008).…”
Section: Fig 1 Transient Gus Expression In European Plum (Prunus Domentioning
confidence: 99%
“…The culture medium is the platform and the fundamental base of transformation. Medium can be an important factor for plant transformation (Joyce et al 2010). There is not report regarding the effect of different culture media on plum genetic transformation.…”
Section: Fig 1 Transient Gus Expression In European Plum (Prunus Domentioning
confidence: 99%
“…One of the most commonly used auxins for callus induction of grass species is 2,4-d, which was sometimes used in combination with cytokinins such as BA and kinetin. In sugarcane (Joyce et al 2010) and centipedegrass (Yuan et al 2009), callus was efficiently induced on medium supplemented with 2,4-d alone, while 2,4-d together with low level of BA was effective for callus induction in miscanthus (Głowacka et al 2010), bermudagrass (Chaudhury and Qu 2000) and Kentucky bluegrass (van der Valk et al 1995). In the present study, mature seeds of E. ravennae initiated to produce calli within 10 days of culture in the dark on almost all the culture media expect for 2,4-d free medium ( Figure 1A (Table 1).…”
Section: Primary Callus Inductionmentioning
confidence: 99%